Altered Monocyte and Endothelial Cell Adhesion Molecule Expression Is Linked to Vascular Inflammation in Human Immunodeficiency Virus Infection. (15th October 2016) - Kulkarni, Manjusha; Bowman, Emily; Gabriel, Janelle; Amburgy, Taylor; Mayne, Elizabeth; Zidar, David A.; Maierhofer, Courtney; Turner, Abigail Norris; Bazan, Jose A.; Koletar, Susan L.; Lederman, Michael M.; Sieg, Scott F.; et al.
Abstract: Background: Human immunodeficiency virus (HIV)-infected individuals have increased risk for vascular thrombosis, potentially driven by interactions between activated leukocytes and the endothelium. Methods: Monocyte subsets (CD14 + CD16 −, CD14 + CD16 +, CD14 Dim CD16 + ) from HIV negative (HIV − ) and antiretroviral therapy-treated HIV positive (HIV + ) participants (N = 19 and 49) were analyzed by flow cytometry for adhesion molecule expression (lymphocyte function-associated antigen 1 [LFA-1], macrophage-1 antigen [Mac-1], CD11c/CD18, very late antigen [VLA]-4) and the fractalkine receptor (CX3CR1); these receptors recognize ligands (intercellular adhesion molecules [ICAMs], vascular cell adhesion molecule [VCAM]-1, fractalkine) on activated endothelial cells (ECs) and promote vascular migration. Plasma markers of monocyte (soluble [s]CD14, sCD163) and EC (VCAM-1, ICAM-1, 2, fractalkine) activation and systemic (tumor necrosis factor receptor [TNFR-I], TNFR-II) and vascular (lipoprotein-associated phospholipase A2 [Lp-PLA2 ]) inflammation were measured by enzyme-linked immunosorbent assay. Results: Proportions of CD16 + monocyte subsets were increased in HIV + participants. Among all monocyte subsets, levels of LFA-1 were increased and CX3CR1 levels were decreased in HIV + participants ( P < .01). Levels of sCD163, sCD14, fractalkine, ICAM-1, VCAM-1, TNFR-II, and Lp-PLA2 were also increased in HIV + participants ( P < .05), and levels of sCD14, TNFR-I, and TNFR-II were directly related to ICAM-1 and VCAM-1 levels in HIV + participants. Expression of CX3CR1 on monocyte subsets was inversely related to plasma Lp-PLA2 ( P < .05 for all). Conclusions: Increased proportions of CD16 + monocytes, cells with altered adhesion molecule expression, combined with elevated levels of their ligands, may promote vascular inflammation in HIV infection.